PENERAPAN METODE EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN MINAT BELAJAR MATA PELAJARAN BAHASA ARAB PADA PESERTA DIDIK KELAS VII DI MTS. KH. HASYIM ASY’ARI SUTOJAYAN MALANG - Balqis Alfi Latifah; Chalimatus Sa’dijah; Yorita Febri Lismanda (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The application of method everyone is a teacher here to increase interest in learning Arabic subject in grade VII at MTs. KH. Hasyim Asy’ari Sutojayan Malang, because of some problems in the learning process. In this research the problems to be discussed are 1) the process of implementing of the method everyone is a teacher here to increase intrest in learning arabic in grade VII at MTs. KH. Hasyim Asy’ari Sutojayan Malang. 2) increased student intrest in learning class VII in Arabic subject at MTs. KH. Hasyim Asy’ari Sutojayan Malang throught the application of the method everyone is a teacher here. This research use descriptive qualitative approach through classroom action research. The source of data comes from observations, interviews, and documentation. The observation that the researchers did, the lack of intrest student following Arabic lessons caused by the lecture method applied made students not actively participating in class because the learning process was dominated by the teacher. Activities shown by students after learning using the method of everyone is a teacher here are in accordance with those mentioned in the indicators of intrest in learning. With the intrest in learning a subject, the learning outcomes obtained are maximum.